ANALISIS MAKNA KONSPETUAL DAN MAKNA ASOSIATIF PADA NOVEL “SI ANAK SAVANA” KARYA TERE LIYE SEBAGAI ALTERNATIF BAHAN AJAR PESERTA DIDIK. - Citra Mawaddah; Rendy Triandy; Eggie Nugraha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the conceptual meaning and associative meaning in the novel "Si Anak Savana" by Tere Liye and its implications for alternative learning materials for students. The method used in this study is descriptive qualitative research. The data sources in this study are several words of conceptual meaning and associative meaning contained in the novel "Si Anak Savana" by Tere Liye. The data collection technique for this study uses text analysis techniques by reading the novel "Si Anak Savana" by Tere Liye. From the analysis of this novel, it can be concluded that there are several conceptual meanings and associative meanings, and there are 3 things that can be concluded, namely first, the unification of setting and character; second as a medium of social criticism and education; third, a humane moral message. The conceptual meaning and associative meaning in the novel "Si Anak Savana" there are 61 data from 12 parts, then in the associative meaning there are 48 data including the social category and 13 data including the cultural category. This study can also be concluded that analyzing the conceptual meaning and associative meaning in the novel "Si Anak Savana" by Tere Liye as an alternative teaching material for students is very effective because novels are one of the best teaching media for studying literature.